Evaluation of Employees' Knowledge of Colorectal Cancer Prevention and Screening at a Reference Oncology Centre - Andrade de Souza, Karina Quely; Silva, Paulo André Lago; Machado, Dan Perdiz Fucs; David, Gabriel Cury Andari; de Abreu, Glicia Estevam (Journal of Coloproctology, 2024)
Introduction Despite the high prevalence and severity of colorectal cancer (CRC), the public is mostly unaware of its prevention and screening.Objective To determine the level of knowledge regarding CRC prevention and screening among staff at a reference cancer center.Materials and Methods A cross-sectional study was conducted in a reference cancer center. Employees aged 18 and up who had worked at the oncology center for at least one year were given a questionnaire containing sociodemographic and evaluative questions about CRC prevention and screening.Results The sample comprised 266 employees, with a median age of 45 (53.00–35.75) years of age. Most of the staff (76.3%) were female, had at least a year of experience at the health facility (74.1%), and agreed on the definition of CRC. Inflammatory bowel illness was the least commonly recognized risk factor (67.6%). Most of the sample (56%) recognized all 5 warning flags. Colonoscopy was the most popular screening test (98.7%). Although the health center does not offer official CRC education, most of the staff (42.1%) reported learning about CRC while working.There was no difference in perceptions of the optimal age to begin screening between employees 45 years or older and those younger (p = 0.729). Higher-educated employees were more knowledgeable about CRC (p = 0.001).Conclusion In a reference cancer center, the staff members who work directly with patients as well as those with higher levels of schooling have a satisfactory level of knowledge regarding CRC prevention and screening.
Keywords: colorectal cancer; screening; prevention; risk factor; knowledge